(3GdeUHGM aj Yjhf GdUMGMs - (3YHO GdZfj Hf YHO GdhGMO Hf Ydj Hf SQhQ GdebOSj GdLeGYjdj GdOeTbj GdMfHdj, CHh eMeO, Jbj GdOjf,J (B600 (3g` s
(3ChdgG (B:s
(3Chdg MOjK QhGg GdHNGQi Yf Ydi Yf SajGf GHf YjjfI , hgh (B: (3deG bGe QShd Gddg Udi Gddg Ydjg hSde GdeOjfI GSJge GdfGS GdefGRd s
(3BNQgG (B:s
(3jfJgi HMOjK GdEac s
(3Ydjg SeGY HNW GdeDda eDQN HSfI (B596(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B275s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B493 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B103 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MOjK (B1905) s
Keywords: (3GdMOjK h GdeUWdMs